NOVEL APPLICATIONS OF KASIM: HERITAGE MEETS HAUTE COUTURE - Agrawal, Aakanksha; Gupta, Charu; Aggarwal, Sunita Aggarwal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the revitalization of Kasim, a traditional natural dye, through its application in modern fashion. Kasim, a dye historically integral to Indian crafts such as Kalamkari, Bagh, and Ajrakh, has been crafted over generations by fermenting jaggery and iron fillings. When applied to fabric pre-mordanted with myrobalan, it produces a distinct black hue, traditionally used for freehand painting and block printing of design outlines. To bring this age-old dye into contemporary relevance, the research developed new application techniques that simplify its use while enhancing its aesthetic possibilities. Various methods, including leaf printing and resist spraying, were tested to achieve sophisticated design effects suitable for haute couture. The study culminated in the design of a collection of kaftan kurtas, conceptualized using CAD software, with strategically placed prints on areas such as the shoulders, hemline, and neckline. This precise placement not only enhances the visual appeal of the garments but also aligns with current minimalist fashion trends, making Kasim both relevant and attractive to today’s fashion consumers. The innovative designs generated in this research demonstrate the seamless integration of traditional dyes into modern fashion, offering a valuable pathway for designers and manufacturers to incorporate cultural heritage into contemporary products while meeting the expectations of modern markets.